Migration and new media : transnational families and polymedia - Madianou, Mirca; Miller, Daniel, 1954- (Abingdon, Oxon ; New York : Routledge, 2012)
Summary:
"The way in which families maintain long distance communication when they are separated because of migration has been revolutionised by the emergence of a variety of internet- and mobile phone-based platforms. These platforms have created a new communicative environment, which the authors call 'polymedia'. This book draws on a long-term ethnographic study of prolonged separation between transnational Filipino migrant mothers in the UK and their left-behind children in the Philippines. It is unique in the way it provides firstly a theory of the new experience of media itself, as polymedia. This is complemented by a theory of relationships based on an analysis of mother-child communication. The authors seek to go beyond both media studies and anthropology to construct a new theory of mediated relationships that combines findings from both disciplines and has considerable importance for the social sciences more generally."--Publisher's description.
Sadržaj:
The Philippines and globalisation : migration, mothering and communications -- Why they go and why they stay -- Letters and cassettes -- The mothers' perspective -- The children's perspective -- The technology of relationships -- Polymedia -- A theory of mediated relationships.
Includes bibliographical references and index.
Keywords: Filipini; obitelj; radnička klasa; migracije